Dos preguntas para un recuerdo: interrogantes para abordar las memorias de infancia durante las últimas dictaduras en Argentina y Uruguay - Fira Chmiel (Centre de Recherches sur les Mondes Américains, 2021)
The following text presents a critical reading of the works that attend the generational perspective of the memorial field in Argentina and Uruguay. From a bibliographic review, two key questions that articulate two analytical approaches are explored. The first is about the dimension of experience and the second, about the symbolic productions that narrate these experiences. In these approaches we find tensions, debates, positions, that reflect the ways in which childhoods were part of the past. In particular, the ways in which boys and girls experienced the ferocity of dictatorships in Argentina and Uruguay.